2019
DOI: 10.18203/2319-2003.ijbcp20194280
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction reporting in a tertiary care teaching hospital in eastern India: a retrospective study

Abstract: Background: Adverse drug reactions (ADRs) are one of the prime causes of morbidity and mortality, increase in hospital stay and socioeconomic burden on the patients. Periodic monitoring aids in formulating methods for safe usage of medicines in hospitals. This study was undertaken to study the patterns, assessment of causality, severity, preventability, body systems affected from ADRs received by the Pharmacovigilance cell, Department of Pharmacology between April 2018 to June 2019.Methods: The present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…Female preponderance (60.5%) was noted among the cases, similar to a study by James and Rani 10 (60%) and Godbharle and Padwal 11 showing that females may have more risk of developing ADRs. In our study, the adult age group (31–45 years) reported the majority of ADRs (27.2%), which was comparable to a study by Misra et al 5 (42.8%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Female preponderance (60.5%) was noted among the cases, similar to a study by James and Rani 10 (60%) and Godbharle and Padwal 11 showing that females may have more risk of developing ADRs. In our study, the adult age group (31–45 years) reported the majority of ADRs (27.2%), which was comparable to a study by Misra et al 5 (42.8%).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the frequently affected organ system was found to be the dermatological (68.4%) with a predominance of cutaneous manifestations (itching and rashes) (29.8%), similar to studies by James and Rani (75%), 10 Godbharle and Padwal (34.4%) 11 and Misra et al (51.1%), 5 but a study by Venkatasubbaiah et al 1 and Joseph and Badyal, 12 showed the most commonly affected system was gastrointestinal system followed by skin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result was somewhat in concordance with some previous studies. 12 Adverse drug reactions have been reported to occur mainly in young and middle-aged adults. Reason could be that the patients of this age group are more prone to diseases, are often on multiple drug therapy and frequently visits the outpatient department for their regular check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to findings of numerous previous studies. 12,[16][17][18][19] The reason could be that antimicrobials are the most common class of drugs to be used in hospital settings. So, the chances of ADRs being reported due to them are also high.…”
Section: Discussionmentioning
confidence: 99%